Age variations and population over-coverage: Is low mortality among migrants merely a data artefact?. (2nd January 2022) - Wallace, Matthew; Wilson, Ben
Abstract : The migrant mortality advantage has been observed extensively, but its authenticity is debated. In particular, concerns persist that the advantage is an artefact of the data, generated by the problems of recording mobility among foreign-born populations. Here, we build on the intersection of two recent developments: the first showing substantial age variation in the advantage—a deep U-shaped advantage at peak migration ages—and the second showing high levels of population over-coverage, the principal source of data artefact, at the same ages. We use event history analysis of Sweden's population registers (2010–15) to test whether this over-coverage can explain age variation in the migrant mortality advantage. We document its U-shape in Sweden and, crucially, demonstrate that large mortality differentials persist after adjusting for estimated over-coverage. Our findings contribute to ongoing debate by demonstrating that the migrant mortality advantage is real and by ruling out one of its primary mechanisms.